1983
DOI: 10.1677/joe.0.0960259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the anterior pituitary gland and gonads on enzyme components of the hepatic microsomal cytochrome P-450 system of male and female rats

Abstract: The concentration of cytochrome P-450 in microsomes prepared from the livers of mature female Wistar-derived rats was significantly lower than in mature males. This sex difference was abolished after hypophysectomy, when the concentration of the cytochrome in males and females was not significantly different from that in the intact male. A concentration of cytochrome P-450 characteristic of females was restored by two anterior pituitary transplants under the kidney capsule of hypophysectomized females; a parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1985
1985

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Previous studies by Gillham, Hutchinson & Thorn (1983) suggested that cyto¬ chrome b5, ferricyanide and NADPH-cytochrome c reductase might be hormonally regulated independ¬ ently of the cytochrome P-450 regulator system. Thus, under varying hormonal conditions, changes in cytochrome P-450 concentrations might occur without changes in other mixed function oxidase enzymic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by Gillham, Hutchinson & Thorn (1983) suggested that cyto¬ chrome b5, ferricyanide and NADPH-cytochrome c reductase might be hormonally regulated independ¬ ently of the cytochrome P-450 regulator system. Thus, under varying hormonal conditions, changes in cytochrome P-450 concentrations might occur without changes in other mixed function oxidase enzymic activities.…”
Section: Discussionmentioning
confidence: 99%